Relationship of stress on the eating behaviours of auxiliary police officers in Selangor / Nur Atika Mhd Razali - Mhd Razali, Nur Atika (2016)
Auxiliary police officers are exposed to many types of stressors as part of their professional duties. Prolonged life stress may be linked to various bad health status. Therefore, this study aimed to determine the nutritional status, stress level and eating behaviour of auxiliary police officers in Selangor with their relationships. One hundred thirteen auxiliary police officers completed the nutritional assessment, the Depression, Anxiety and Stress Scale (DASS) questionnaire and the Three-Factor Eating Questionnaire-R18 (TFEQ-R18). Data analysis is done using SPSS version 21.0 software included descriptive statistic, parametric statistics, and Pearson's correlation test. For DASS scale, most of auxiliary police officers had normal level of depression, anxiety and stress scores which are 48.7%, 39.8% and 46.9%. All of the auxiliary police officers had low cognitive restraint and uncontrolled eating (100.0%), while most of them had low emotional eating (43.4%). Unfortunately there was no statistical differences were found neither in the depression, anxiety and stress scores or cognitive restraint, uncontrolled eating and emotional eating among auxiliary police officers with different variables tested such as age category, gender, marital status, educational level, household income, working shift, BMI levels, blood pressure and smoking status (p>0.05). Study was found all positive correlation between DASS and TFEQ-R18 scores with uncontrolled eating showed the most significant correlation scores with the depression, anxiety and stress scores respectively (rs= 0.286, p= 0.002; rs= 0.272, p= 0.004; rs= 0.258, p= 0.006). However, all of the significant correlation showed fall within fair strength of correlation between the variables based on the (rs) coefficient of correlation. As lack of primary sources of auxiliary police officers, this study is meant to become one of the pioneer research in this area.